New polymer electrolytes of bio-based polyurethane for dye-sensitized solar cell applications / Salmiah Ibrahim - Salmiah, Ibrahim (2016)

(untitled)
In this research work, a new bio-based polyurethane (PU) based on castor oil was synthesized as host polymer in electrolytes for application in dye-sensitized solar cell (DSSC). In the first stage of this work, castor oil based polyol was synthesized via transesterification reaction under nitrogen gas atmosphere at room temperature. The polyol possessed acid value of 3.0 mg KOH g−1, hydroxyl value of 190 mg KOH g−1 and molecular weight of 2786 g mol−1, characteristics suitable for producing flexible PU. The polyol was reacted with 4,4’-diphenylmethane diisocyanate at room temperature in appropriate ratios to form flexible PU. The formation of urethane linkage was confirmed using Fourier transform infrared analysis by the disappearance of NCO peak and appearance of amine (secondary), carbonyl and ether group in PU chain. For the preparation of PU polymer electrolytes, the PU was added with sodium iodide (NaI) and lithium iodide (LiI) salts in different weight percentages to form PU-LiI and PU-NaI systems respectively. 3-propyl-1-methylimidazolium iodide (PMII) ionic liquid was added to the highest conducting sample of PU-NaI and PU-LiI systems to enhance the conductivity as well as the efficiency of DSSC. The characteristics of polymer electrolytes were analyzed using Fourier transform infrared spectroscopy, dynamic mechanical analysis, electrochemical impedance spectroscopy, transference number measurement and linear sweep voltammetry. Glass transition temperature of –15.8 °C of PU decreased upon addition of salts. The lowest glass transition temperature of PU-NaI system was –26.2 °C and PU-LiI system was –27.3 °C. The highest conductivity achieved for the systems were 4.28 × 10−7 S cm−1 and 1.41 × 10−6 S cm−1, respectively. The inclusion of PMII ionic liquid to the PU-NaI and PU-LiI enhanced the ionic conductivity of the polymer electrolytes by one order of magnitude and also lowered the Tg value to ~ –33.0 °C. Ionic liquid is believed to act as plasticizer to soften the polymer backbone iv therefore increase the polymer segmental motion to ease ions migration which in turn increased the ionic conductivity. The conductivity for all PU electrolyte films increased with increase of temperature and follow the Arrhenius behaviour for PU-NaI, PU-LiI and PU-NaI-PMII systems, and Vogel-Tamman-Fulcher behaviour for PU-LiI-PMII. The calculation of activation energy, Ea from the gradient of Arrhenius and Vogel-Tamman- Fulcher plots showed that the trend of conductivity was consistent with the trend of Ea, i.e: the higher conducting sample possessed lower activation energy. The addition of ionic liquid to the PU-salt also enhanced electrochemical stability window of the polymer electrolytes. The electrochemical stability windows were ~ 2.0 V. DSSCs were fabricated employing PU based polymer electrolytes with configuration of FTO/TiO2-dye/PU electrolytes-I2/Pt/FTO. Photovoltaic parameters such as current density, open circuit voltage, fill factor and efficiency were calculated from photocurrent–voltage measurement. The highest efficiency employing PU-NaI and PU-LiI systems were 0.80% and 0.83%, respectively, whereas for PU-NaI-PMII was 1.06% and PU-LiI-PMII was 1.92%. These results revealed that the new bio polymer electrolytes have potential for application in DSSC.